2018
DOI: 10.1177/0363546518765158
|View full text |Cite
|
Sign up to set email alerts
|

Summative Report on Time Out of Play for Major and Minor League Baseball: An Analysis of 49,955 Injuries From 2011 Through 2016

Abstract: Contrary to prior reports relying on disabled list data, the annual number of injuries in professional baseball remained steady from 2011 to 2016. Similar trends were noted for the annual number of days missed and mean days missed per injury. Although the mean days missed per injury was high (16), the median was much lower at 6 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
186
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(192 citation statements)
references
References 19 publications
6
186
0
Order By: Relevance
“…22,44 Although popularity in both countries has led to more players participating throughout the multiple levels of baseball, this has also led to an increase in athletic exposures and injuries in the sport. In US professional baseball, major and minor league players are unable to play approximately 120,000 days each year, 4 including about 30,000 days on the Major League Baseball (MLB) disabled list. 7 Of particular concern is the number of throwing arm injuries.…”
mentioning
confidence: 99%
“…22,44 Although popularity in both countries has led to more players participating throughout the multiple levels of baseball, this has also led to an increase in athletic exposures and injuries in the sport. In US professional baseball, major and minor league players are unable to play approximately 120,000 days each year, 4 including about 30,000 days on the Major League Baseball (MLB) disabled list. 7 Of particular concern is the number of throwing arm injuries.…”
mentioning
confidence: 99%
“…We found that the most injured site was the hamstrings, as observed in other reports as well. [1][2][3]5,[7][8][9]12,15,16 The cause of muscle strain was most often base-running during games. In this motion, the runners step on a base while they stretch their feet forward and, consequently, overstretch the hamstrings.…”
Section: Discussionmentioning
confidence: 99%
“…5 Most studies involving muscle strains in professional sports have been conducted in contact sports involving running and kicking 3,8,[15][16][17] ; studies involving professional baseball are relatively rare. Camp et al 2 analyzed 50,000 injuries occurring during 6 seasons in Major and Minor League Baseball players and found that injuries to the upper extremity occurred in 39% of cases, whereas injuries to the lower extremity occurred in 35% of cases. Of those injuries, the most common was hamstring strain.…”
mentioning
confidence: 99%
“…Although the injury patterns of MLB athletes have been described previously, there is little understanding of the impact of injuries sustained by athletes before entering the MLB draft. 1,4,16,19,21 Knowledge of these data may help improve decision making by medical, coaching, and franchise personnel prior to drafting these athletes. This study assessed all predraft MLB prospects and compared those who were noninjured (22.8%), had nonoperatively treated musculoskeletal injuries (48.8%), and had operatively treated musculoskeletal injuries (28.5%) over a 5-year period.…”
Section: Discussionmentioning
confidence: 99%